The Potential Difference Characteristics between Two Points on Grounding Grid of Substation - Yonghong WANG; Chongqing JIAO; Bing XIAO; Anqi GUO; Guizhong QIU; Lipeng BI; Keqiang XU (Zhongguo dianli)
With the intelligentization upgrade of power substations, a large number of secondary equipment are deployed dispersedly nearby the high-voltage primary equipment. The enclosures of these secondary devices are electrically connected to the grounding grid underground. When a fault current injection causes the potential rise in the grounding grid, there is a potential difference between any two points on the grounding grid conductors. For two secondary equipment located at different positions and connected by secondary cable, the potential difference can induce common-mode and differential-mode disturbance voltages at the ports of the secondary cable, which may interfere the normal operation of secondary system. In this paper, the grounding grid of a 220 kV substation is modelled and the corresponding potential difference is calculated by using the CDEGS software. Also, the effects of the grid density and size, soil resistivity, the positions of current injection and potential observation on the potential difference are investigated. The results are helpful for guiding grounding grid design and evaluating the influence of ground potential difference on secondary equipment.